Development of gross motor capacity and mobility performance in children with cerebral palsy: a longitudinal study. (20th November 2021) - Burgess, Andrea; Reedman, Sarah; Chatfield, Mark D; Ware, Robert S; Sakzewski, Leanne; Boyd, Roslyn N
Abstract : Aim: To describe development of gross motor capacity and mobility performance in children with cerebral palsy. Method: This longitudinal cohort study measured gross motor capacity with the Gross Motor Function Measure and mobility performance with the Pediatric Evaluation of Disability Inventory (PEDI) between 18 months and 5 years, and the PEDI – Computer Adaptive Test (PEDI‐CAT) between 8 years and 12 years. Longitudinal analyses used mixed‐effects regression modelling with interaction between age and Gross Motor Function Classification System (GMFCS). Stability of GMFCS levels over time was measured using agreement. Results: Two hundred and twenty‐two children provided 871 observations (median 4 observations, range 1–7). Children classified in GMFCS level I improved in both capacity and performance until 8 to 12 years. Children classified in GMFCS levels II and III continued to develop mobility performance after gross motor capacity had plateaued at 5 years. Children classified in GMFCS level IV plateaued at 5 years in capacity and performance. Children classified in GMFCS level V showed no changes in capacity or performance between 18 months and 8 to 12 years. Stability of GMFCS levels was 73%. Interpretation: Change in mobility performance over time somewhat reflected gross motor capacity trajectories. Continued improvement in mobility performance after plateau of gross motor capacity for children classified in GMFCS levels II and III suggests importance of other personal or environmental factors.